Po sledeh in na novih poteh raziskovanja kulture in religij - Velikonja, Mitja (Teorija in praksa, 2014)
The article summarises in a concise and analytical way the history of the Centre for Cultural and Religious Studies from its establishment in 1967 in both the academic and broader socio-historical contexts. In addition, it considers its future development within the Faculty of Social Sciences of the University of Ljubljana, and consequently also the development of religious and cultural studies in Slovenia in general. After introducing other articles in this special issue, it in particular explains the research results of the Centre (and fields of study that remain unresearched), the connection with the development of the Department of Cultural Studies, its past and present members and its international cooperation and successes.
Keywords: Center za proučevanje kulture in religije; Culturology; Historical reviews; Kulturologija; scientific method; Scientific research; Slovenia; Slovenija; Sociologija religije; Sociology of religion; Zgodovinski pregledi; Znanstveno raziskovanje